The Influence of Quality of Work Life (QWL) on Employee Performance Through Organizational Citizenship Behavior (OCB) in the Emergency Department - Nafira Junaedi; Rahmat Bahtiar; Riyan Ningsih; Indah Puspitasari; Irfansyah Baharuddin Pakki; Akhmad Azmiardi (Indonesian Journal of Global Health Research, 2025)
Achieving good employee performance requires a positive and conducive Quality of Work Life (QWL), which in turn enhances employees Organizational Citizenship Behavior (OCB) at Hospital X in Samarinda. Therefore, employees with high QWL and OCB are needed to improve hospital services. The purpose of this study is to determine and analyze the influence of Quality of Work Life on employee performance through Organizational Citizenship Behavior (OCB) as an intervening variable.This research is a quantitative study using an observational approach with a cross-sectional design. Primary data were collected through questionnaires distributed to 138 employees in the Emergency Department of Hospital X in Samarinda. Data were analyzed using SmartPLS 4.0 software.The results showed that the p-value of the Quality of Work Life variable was 0.00 < 0.05, indicating that QWL has a direct and positive effect on employee performance with a coefficient of 0.409 (40.9%). The p-value for QWL was 0.000 < 0.05, meaning QWL has a direct and positive effect on Organizational Citizenship Behavior with a coefficient of 0.611 (61.1%). The p-value for OCB was 0.000 < 0.05, indicating that OCB has a direct and positive effect on employee performance with a coefficient of 0.421 (42.1%). The p-value for QWL was 0.000 < 0.05, showing that QWL has an indirect and positive effect on employee performance through OCB with a coefficient of 0.257 (25.7%).It is recommended that the management of Hospital X in Samarinda improve employee performance by enhancing the Quality of Work Life first or through the development of Organizational Citizenship Behavior.